Predicatori nelle terre slavo-orientali (XI-XIII sec.) Retorica e strategie comunicative - ROMOLI, FRANCESCA (Biblioteca di Studi Slavistici, 2009)
The book offers an overview of homiletic literature in the Kievian period (XI-XIII century) through the figures of four preachers: the Metropolitan Nikifor I († 1121), Serapion Vladimirskij († 1275), Luka Židjata († 1059) and the hegumen Moisej († 1187). Adopting an approach that, on the one hand takes into consideration the methods recently applied to the study of Western and Byzantine mediaeval homiletics, and on the other recent studies addressing the rhetorical form and the use of citations, the author investigates the function of the Biblical and liturgical citations in the texts of the Slavic-Oriental homiletic tradition, proposing an interpretation in a key that is not merely rhetorical but also linked to pragmatic linguistics.